Pengaruh Persentase Ampas Kopi Robusta (Coffea canephora) dan Suhu Pemanasan terhadap Karakteristik Body Scrub - Pribadi, Thisia Anggraeni; Hasojuwono, Bambang Admadi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p10, 2021)
Body scrub is one of the cosmetic products used for skin care. Body scrubs have coarse granules that function to remove dead skin cells and clean the skin optimally, which is called abrasive or sanding. This study aims to determine the effect of the percentage og coffee grounds and heating temperature and their interaction on the characteristics of the body scrub and to determine the percentage of coffee grounds and the right heating temperature so as to produce a body scrub with the best characteristics. This study used a factorial randomized block design with two factors. The first factor is the percentage of coffee grounds with 3 levels, namely 4, 6 and 8%, while the second factor is the heating temperature with 3 levels, namely 65, 70 and 75?C. The results showed that the percentage of coffee grounds had an effect on ph, viscosity, spreadability, adhesion, total phenolic compounds and overall body scrub acceptance. The heating temperature affects the viscosity, spreadability, adhesion, total phenolic compounds and overall acceptance of the body scrub but the heating temperature has no effect on the ph of the body scrub. The interaction between the percentage of coffee grounds and the heating temperature had no effect on ph, viscosity, spreadability, adhesion, total phenolic compounds and overall acceptance of the body scrub. The percentage of 4% coffee grounds and a heating temperature of 65?C is the best treatment of body scrub with characteristics of ph 5.93, viscosity of 7600 cp, dispersion of 5.6 cm, adhesion of 5.78 seconds, separation ratio = 1, total phenolic compounds 1.52 mg GAE/g and overall acceptance was 4.95 (regular to moderate). Keywords : body scrub, coffee ground, heating temperature